Spirituality among family caregivers of cancer patients: The Spiritual Perspective Scale. Issue 4 (9th June 2020) - La, In Seo; Johantgen, Meg; Storr, Carla L.; Cagle, John G.; Zhu, Shijun; Ross, Alyson
Abstract: Spirituality is a critical resource for family caregivers of patients with cancer. However, studies on spirituality are hampered because measures of spirituality lack consistency and have not been validated in cancer caregivers. This study examined the validity of the Spiritual Perspective Scale (SPS) among cancer caregivers and explored whether measurement bias may influence differences in spirituality across caregiver and patient characteristics. In this secondary analysis, 124 caregivers of cancer patients were used to evaluate the validity of the 10‐item SPS. A multiple indicators multiple causes model was applied to explore differences in the association between a latent spirituality factor and characteristics of caregivers and patients. Overall reliability of the SPS was adequate (Cronbach's α = .95). The SPS scores were predictive of higher meaning and purpose ( r = .32, p = .004) and lower depression ( r = −.22, p = .046) at 3‐month follow‐up. Construct validity of the SPS with a single‐factor structure was supported in cancer caregivers. Adjusting for a direct effect of race did not alter the pattern of results, and caregivers who were older, female, ethnic minorities, less‐educated, affiliated with a religion, and who provided care to another individual in addition to the patient had greater levels of spirituality. This study provides evidence for psychometric validation of the SPS in cancer caregivers. Understanding differences in caregivers' spirituality by using the SPS with psychometrically acceptable properties and minimal measurement bias deserves more attention to optimize spirituality assessment and support in cancer caregiving.